The Effectiveness Of Wordwall Game As Media To Teach Students' English Vocabulary Mastery Of Eighth-Grade - Nurammida, Nurammida; Nizarrahmadi, Nizarrahmadi; Yolanda, Alvina (CV. Jendela Edukasi Indonesia, 2024)
This study evaluates the effectiveness of Wordwall Media as a game-based learning tool for teaching English vocabulary mastery to eighth-grade students at MTS Al Hadari An-Nawawi. Using a quantitative pre-experimental approach with a one-group pretest-posttest design, the research involved 30 female students. The results indicate a significant improvement in vocabulary mastery, with an average pretest score of 56.43 and a posttest score of 74.67. Statistical analysis revealed a T-Count value (-11.345) that was greater than the T-Table value (1.699), indicating a statistically significant difference. The null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted, demonstrating a significant difference following the intervention. In conclusion, the use of Wordwall Media as a game-based learning method produced positive results in English vocabulary mastery for students. This research supports the use of game technology as an innovative educational method that provides a more dynamic and interactive learning experience, motivating students to be more engaged in the learning process.